Factors promoting nursing leadership in health care settings: a theoretical perspective - Šabanovič, Beatričė; Jakavonytė-Akstinienė, Agnė (Slauga. Mokslas ir praktika, 2022)
This article presents a theoretical study on the factors that promote nursing leadership in healthcare settings. Leadership in healthcare settings is significant because the success of an organisation depends to a large extent on the personal qualities of its leaders. Leadership is not only a managerial activity, but also a competency that can be important both in the management of the organisation and at all levels of the organisation. The aim of this paper is to review and present the factors that promote nursing leadership in healthcare settings. Methods – Systematic search of PubMed, Cochrane Library and Google Scholar. The systematic review included 14 articles on the topic. The results showed that leadership is associated with organisational success. The main factors for promoting nurses’ leadership are: organizational leadership endorsement by managers, initiating change, organizing nurses around leadership issues, promoting communication, creating an environment conducive to leadership development, financial support and motivation, decision-making freedom, and creating opportunities to care for oneself and colleagues.